Ecological adaptation of earthworms for coping with plant polyphenols, heavy metals, and microplastics in the soil: A review. Issue 3 (March 2023) - Gudeta, Kasahun; Kumar, Vineet; Bhagat, Ankeet; Julka, Jatinder Mohan; Bhat, Sartaj Ahmad; Ameen, Fuad; Qadri, Humaira; Singh, Sumit; Amarowicz, Ryszard
Abstract: In recent years, soil pollution by massive accumulation of heavy metals (HMs), microplastics, and refractory hydrocarbon chemicals has become an emerging and global concern, drawing worldwide attention. These pollutants influence soil diversity by hindering the reproduction, abundance, thereby affecting aboveground productivity. The scientific community has recently emphasized the contribution of earthworms to heavy metal accumulation, microplastic degradation, and the decomposition of organic matter in the soil, which helps maintain the soil structure. This review paper aimed to compile scientific facts on how earthworms cope with the effect of HMs, microplastics, and plant polyphenols so that vermiremediation could be widely applied for well-being of the soil ecosystem by environmentalists. Earthworms have special surface-active metabolites in their guts called drilodefensins that help them defend themselves against the oxidative action of plant polyphenols. They also combat the effects of toxic microplastics, and other oxidative compounds by elevating the antioxidant activities of their enzymes and converting them into harmless compounds or useful nutrients. Moreover, earthworms also act as biofilters, bioindicators, bioaccumulators, and transformers of oxidative polyphenols, microplastics, toxic HMs, and other pollutant hydrocarbons. Microorganisms (fungi and bacteria) in earthworms' gut of also assist in the fixation, accumulation, and transformation of these toxicants to prevent their effects. As a potential organism for application in ecotoxicology, it is recommended to propagate earthworms in agricultural fields; isolate, and culture enormously in industry, and inoculate earthworms in the polluted soil, thereby abate toxicity and minimizing the health effect caused by these pollutants as well enhance the productivity of crops.